Influence of Marching Band Experience on Eating Disorder Risk and Perceived Stress in Collegiate Marching Artists - Kalor Greve; Jaclyn Caccese; Matthew Brancaleone (Journal of Sports Medicine and Allied Health Sciences: Official Journal of the Ohio Athletic Trainers' Association)
Introduction: Collegiate marching artists face severe and prevalent stressors that may contribute to poor mental health and unhealthy habits. The purpose of this study was to determine the effect of sex and years of participation in collegiate marching band on the relationship between eating disorder risk and perceived stress levels. Methods: Marching artists from an NCAA Division I university completed the Eating Disorder Questionnaire-6 (EDEQ-6) and Perceived Stress Scale (PSS-10) to obtain disordered eating behaviors and perceived stress levels, respectively. Spearman rank correlations were used to determine the relationship between PSS-10 scores and global and subscale EDEQ-6 scores, and the relationship between years of participation in collegiate marching band and PSS-10 and EDEQ-6 scores. Mann-Whitney U tests were used to determine effect of sex on PSS-10 and EDEQ-6 scores. Results: Seventy-one marching artists participated. Positive correlations existed between PSS-10 scores and Global EDEQ-6 scores (r=0.31, p=0.01), EDEQ-6 Eating Concern (r=0.32, p=0.01), EDEQ-6 Shape Concern (r=0.31, p=0.01), and EDEQ-6 Weight Concern (r=0.31, p=0.01). There was a significant effect of sex on Global PSS-10 score (p=0.01), EDEQ-6 Shape Concern (p=0.01), and Global EDEQ-6 score (p=0.02). Discussion: Greater perceived stress may be correlated with eating disorder concerns and risk due to changes in coping mechanisms and body dissatisfaction. Females may report higher perceived stress and eating disorder concerns due to emotional-based coping and avoidance strategies. Collegiate marching artists may have a high chance of developing eating or other psychological disorders and future research should use more screening methods to fully understand the risk.